Novel Mutation Detection of an Inflammatory Molecule Elastase ii Gene Encoding Neutrophil Elastase in Kostmann Syndrome - G. Ahangari; Z. Chavoshzadeh; Z. Lari; A. Ramyar; A. Farhoudi (European Journal of Inflammation, 2007)
Severe congenital neutropenia (SCN), often referred to as Kostmann syndrome, is a rare immune deficiency syndrome diagnosed at or soon after birth, characterized by maturation arrest of myeloid cells at the promyelocyte stage of hematopoiesis. In severe congenital neutropenia due to disorder of neutrophil production, patients are predisposed to recurrent bacterial infections. Recently, there have been reports of detected mutations in neutrophil elastase II (ELA2) gene in genomic DNA of severe congenital neutropenia. In this study we attempted to determine whether there is any mutation in elastase II gene encoding. Peripheral blood was collected from five patients with severe congenital neutropenia and 20 healthy individuals. Total RNA was isolated using RNA standard techniques from fresh separated cells by Polymorphoprep. RNA was analyzed by employing PCR amplification of reverse transcribed using a total of ten specific primers. We amplified five exons of ELA2 gene separately and sequenced each exon. Mutational analysis was performed by directed capillary sequencing method. We found mutations in all severe congenital neutropenia patients and no mutation in 20 healthy individuals. The most mutations were in exon 4 and no mutation was found in exons 3 and 5.